Why Should We Care About Care? : The Role of Informal Childcare and Eldercare in Aging Societies - World Bank Group (World Bank, Washington, DC, 2015)
Without appropriate policies to address the expected rise in the care burden, population aging can reduce womens access to economic opportunities and decelerate future growth, thereby threatening the agenda of poverty reduction and shared prosperity in Europe and Central Asia. Based on the analysis of existing and newly collected quantitative and qualitative data, several key policy recommendations can be formulated for policymakers consideration: (a) improvement of the accessibility, affordability, and quality of formal childcare and eldercare options offers a way to address challenges related to excessive reliance on informal care and to capitalize on current opportunities; (b) the design of future demographic, health, and education policy reforms should take into account any potential effects on informal care providers; (c) care leave (both paid and unpaid) can shape families choices about care and market work; (d) flexible work arrangements can function as effective alternatives to unpaid leave; and (e) care-related allowances (both in-kind and cash) aim to promote quality care for children and elders and recognize the work of caregivers but may have negative repercussions on caregivers labor force outcomes. Increased recognition of the critical role of care in aging societies and careful review of the policy environment related to formal and informal care provision can help governments to harness the full potential of demographics, thereby promoting poverty reduction and shared prosperity.